The individual and organizational predictors of perceived environmental performance and the moderating role of organizational culture among the employees in Malaysian ISO 14001 certified manufacturing companies. - Hajikhani, Maryam (2015)
There are empirical evidences that show the importance of human resource and its associated factors in companies’ environmental performance improvement. However, as the results of these studied show, not much attention has been given to the specific areas of human resource development such as management leadership style, employees work motivation, employees’ environmental training and their specific organizational citizenship behavior towards the natural environment (OCBE) with regard to their contribution to the organizational environmental performance, in particular in developing societies like Malaysia. Accordingly, this study is set to develop an inclusive model of the antecedents of a firm’s perceived environmental performance in presence of organizational culture as a moderating variable. In this study, an integrated model of the theories of socio-technical system (STS) and resource-based view of firm (RBV) were applied to explain the research framework. STS approach generally talks about the importance of technical and social parts of an organization in achieving the system’s goals and objectives. Based on STS, in presence of the technical part, specific consideration needs to be paid to the social part parameters, in order to increase efficiency and performance of the organization. Thus, according to STS the factors of leadership style, motivation, environmental training, OCBE as the parameters of the social part have contribution to the organizational performance. RBV generally stands for the importance of the three kind of resources of an organization including, tangible, intangible and organizational related resource in achieving company’s efficiency and competitiveness. Moreover, based on RBV a company’s organizational related resource (i.e. organizational culture) can increase or decrease the effects of other resources on company’s performance. Thus, it could be stand for the moderating role of organizational culture on the relationship between the mentioned predictors in this study and perceived environmental performance. The present study was completed through a survey on 309 employees (knowledgeable and involved in company’s green issues) from 17 ISO 14001 certified manufacturing companies throughout the Malaysia. The ISO 14001 certified manufacturing companies have been chosen as they are supposed to apply green practices and improve and maintain their environmental efficiency and performance. Doing so, the SEM method was applied to gain the best-fitted model. The goodness of fit measures indicates a satisfactory fit of the hypothesized model. As a result, the model was able to clarify the relationship between independent (exogenous) variables (work motivation (intrinsic, extrinsic), leadership style (transformational, transactional), organizational citizenship behavior towards the environment (OCBE) and environmental training) and perceived environmental performance of the mentioned companies. It also explains the moderating role of organizational culture on the relationship between aforementioned variables and perceived environmental performance. Testing of the proposed hypotheses was done using the correlation coefficients and structural equation modeling (SEM). The final results of this study indicated that there are significant positive relationships among the intrinsic motivation, transformational leadership, organizational citizenship behavior towards the environment (OCBE), environmental training and perceived environmental performance. Transactional leadership style and extrinsic motivation were also significantly associated with perceived environmental performance in presence of organizational culture. Also, the results show that the proposed model is able to explain about 68% of variance of perceived environmental performance (R = 0.68). One important finding of this research is that the three types of the CVF model of organizational culture applied in this study (Clan, Adhocracy, and Market), generally moderate the relationship between aforementioned independent variables and perceived environmental performance. Therefore, companies’ managers, policy makers and practitioners should consider their organizational culture to be favorable and enhancing, when they are practicing green initiatives to increase their environmental performance. The results show some characteristics of organizational culture moderate and reinforce the effects of human resource on the company’s perceived environmental performance. In conclusion, the findings shows that intrinsic motivation, transformational leadership, organizational citizenship behavior towards the environment (OCBE) and environmental training are significant predictors of perceived environmental performance. Moreover, the results have contribution to theory and practice. The findings contributed to the body of knowledge by supporting and expanding the theories of STS and RBV through proposing and integrating of the two theories. It also contributed to the body of knowledge in the area of organizational culture as a moderating variable, work motivation and leadership style as the study tested the factors by their dimensions. The findings also have implications for practice for the mentioned manufacturing companies, their employees and HRD departments.